Effect of ring size on photoisomerization properties of stiff stilbene macrocycles - Olsson, Sandra; Benito Pérez, Óscar; Blom, Magnus; Gogoll, Adolf (Beilstein Journal of Organic Chemistry, 2019)
A series of stiff stilbene macrocycles have been studied to investigate the possible impact of the macrocycle ring size on their photodynamic properties. The results show that reducing the ring size counteracts the photoisomerization ability of the macrocycles. However, even the smallest macrocycle studied (stiff stilbene subunits linked by a six carbon chain) showed some degree of isomerization when irradiated. DFT calculations of the energy differences between the E- and Z-isomers show the same trend as the experimental results. Interestingly the DFT study highlights that the energy difference between the E- and Z-isomers of even the largest macrocycle (linked by a twelve carbon chain) is significantly higher than that of the stiff stilbene unit itself. In general, it is indicated that addition of even a flexible chain to the stiff stilbene unit may significantly affect its photochemical properties and increase the photostability of the resulting macrocycle.
Keywords: DFT; molecular mechanics; photostability; photo-switch; ring-strain; stiff stilbene

(untitled) - Waldeck, D. H. (Chem. Rev., 1991)

(untitled) - Quick, M.; Berndt, F.; Dobryakov, A. L.; Ioffe, I. N.; Granovsky, A. A.; Knie, C.; Mahrwald, R.; Lenoir, D.; Ernsting, N. P.; Kovalenko, S. A. (J. Phys. Chem. B, 2014)

(untitled) - Wang, Y.; Tian, Y.; Chen, Y.-Z.; Niu, L.-Y.; Wu, L.-Z.; Tung, C.-H.; Yang, Q.-Z.; Boulatov, R. (Chem. Commun., 2018)

(untitled) - Zhu, N.; Li, X.; Wang, Y.; Ma, X. (Dyes Pigm., 2016)

(untitled) - Shimasaki, T.; Kato, S.-i.; Ideta, K.; Goto, K.; Shinmyozu, T. (J. Org. Chem., 2007)

(untitled) - Wezenberg, S. J.; Feringa, B. L. (Org. Lett., 2017)

(untitled) - Zhu, H.; Shangguan, L.; Xia, D.; Mondal, J. H.; Shi, B. (Nanoscale, 2017)

(untitled) - O'Hagan, M. P.; Haldar, S.; Duchi, M.; Oliver, T. A. A.; Mulholland, A. J.; Morales, J. C.; Galan, M. C. (Angew. Chem., Int. Ed., 2019)

(untitled) - Wang, Y.; Xu, J.-F.; Chen, Y.-Z.; Niu, L.-Y.; Wu, L.-Z.; Tung, C.-H.; Yang, Q.-Z. (Chem. Commun., 2014)

(untitled) - Yan, X.; Xu, J.-F.; Cook, T. R.; Huang, F.; Yang, Q.-Z.; Tung, C.-H.; Stang, P. J. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Wang, Y.; Sun, C.-L.; Niu, L.-Y.; Wu, L.-Z.; Tung, C.-H.; Chen, Y.-Z.; Yang, Q.-Z. (Polym. Chem., 2017)

(untitled) - Huang, Z.; Yang, Q.-Z.; Khvostichenko, D.; Kucharski, T. J.; Chen, J.; Boulatov, R. (J. Am. Chem. Soc., 2009)

(untitled) - Yang, Q.-Z.; Huang, Z.; Kucharski, T. J.; Khvostichenko, D.; Chen, J.; Boulatov, R. (Nat. Nanotechnol., 2009)

(untitled) - Huang, Z.; Yang, Q.-Z.; Kucharski, T. J.; Khvostichenko, D.; Wakeman, S. M.; Boulatov, R. (Chem. – Eur. J., 2009)

(untitled) - Kucharski, T. J.; Huang, Z.; Yang, Q.-Z.; Tian, Y.; Rubin, N. C.; Concepcion, C. D.; Boulatov, R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Tian, Y.; Kucharski, T. J.; Yang, Q.-Z.; Boulatov, R. (Nat. Commun., 2013)

(untitled) - Li, W.; Edwards, S. A.; Lu, L.; Kubar, T.; Patil, S. P.; Grubmüller, H.; Groenhof, G.; Gräter, F. (ChemPhysChem, 2013)

(untitled) - Stauch, T.; Dreuw, A. (Phys. Chem. Chem. Phys., 2016)

(untitled) - García-Iriepa, C.; Sampedro, D.; Mendicuti, F.; Léonard, J.; Frutos, L. M. (J. Phys. Chem. Lett., 2019)

(untitled) - Fernández-González, M. Á.; Rivero, D.; García-Iriepa, C.; Sampedro, D.; Frutos, L. M. (J. Chem. Theory Comput., 2017)

(untitled) - Blom, M.; Norrehed, S.; Andersson, C.-H.; Huang, H.; Light, M.; Bergquist, J.; Grennberg, H.; Gogoll, A. (Molecules, 2015)

(untitled) - Olsson, S.; Schäfer, C.; Blom, M.; Gogoll, A. (ChemPlusChem, 2018)

(untitled) - Oliverio, M.; Nardi, M.; Costanzo, P.; Cariati, L.; Cravotto, G.; Giofrè, S.; Procopio, A. (Molecules, 2014)

(untitled) - Wang, B.; Zhang, L.; Fu, K.; Luo, Y.; Lu, W.; Tang, J. (Org. Prep. Proced. Int., 2009)

(untitled) - Williamson, A. (London, Edinburgh Dublin Philos. Mag. J. Sci., 1850)

(untitled) - McMurry, J. E. (Chem. Rev., 1989)

Light-Triggered Conformational Switches for Modulation of Molecular Recognition: Applications for Peptidomimetics and Supramolecular Systems - Blom, M. (2015)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Vosko, S. H.; Wilk, L.; Nusair, M. (Can. J. Phys., 1980)

(untitled) - Stephens, P. J.; Devlin, F. J.; Chabalowski, C. F.; Frisch, M. J. (J. Phys. Chem., 1994)

Gaussian 16, Revision B.01 (Gaussian, Inc., 2016)

(untitled) - Miertuš, S.; Scrocco, E.; Tomasi, J. (Chem. Phys., 1981)

(untitled) - Miertus̃, S.; Tomasi, J. (Chem. Phys., 1982)

(untitled) - Pascual-ahuir, J. L.; Silla, E.; Tuñon, I. (J. Comput. Chem., 1994)

(untitled) - Marenich, A. V.; Cramer, C. J.; Truhlar, D. G. (J. Phys. Chem. B, 2009)

(untitled) - Hariharan, P. C.; Pople, J. A. (Theor. Chim. Acta, 1973)

(untitled) - Slavov, C.; Yang, C.; Heindl, A. H.; Stauch, T.; Wegner, H. A.; Dreuw, A.; Wachtveitl, J. (J. Phys. Chem. Lett., 2018)

(untitled) - Cicero, D. O.; Barbato, G.; Bazzo, R. (J. Am. Chem. Soc., 1995)

(untitled) - Norrehed, S.; Johansson, H.; Grennberg, H.; Gogoll, A. (Chem. – Eur. J., 2013)

High-Resolution NMR Techniques in Organic Chemistry - Claridge, T. D. W. (Elsevier, 2009)

(untitled) - Wokaun, A.; Ernst, R. R. (Chem. Phys. Lett., 1977)

(untitled) - Shaka, A. J.; Freeman, R. (J. Magn. Reson. (1969-1992), 1983)

(untitled) - Braunschweiler, L.; Ernst, R. R. (J. Magn. Reson. (1969-1992), 1983)

(untitled) - Davis, A. L.; Keeler, J.; Laue, E. D.; Moskau, D. (J. Magn. Reson. (1969-1992), 1992)

(untitled) - Hurd, R. E.; John, B. K. (J. Magn. Reson. (1969-1992), 1991)

(untitled) - Wagner, R.; Berger, S. (J. Magn. Reson., Ser. A, 1996)

(untitled) - Mohamadi, F.; Richards, N. G. J.; Guida, W. C.; Liskamp, R.; Lipton, M.; Caufield, C.; Chang, G.; Hendrickson, T.; Still, W. C. (J. Comput. Chem., 1990)

(untitled) - Harder, E.; Damm, W.; Maple, J.; Wu, C.; Reboul, M.; Xiang, J. Y.; Wang, L.; Lupyan, D.; Dahlgren, M. K.; Knight, J. L.; Kaus, J. W.; Cerutti, D. S.; et al. (J. Chem. Theory Comput., 2016)

(untitled) - Watts, K. S.; Dalal, P.; Murphy, R. B.; Sherman, W.; Friesner, R. A.; Shelley, J. C. (J. Chem. Inf. Model., 2010)

(untitled) - Zhao, K.-Q.; Chen, C.; Monobe, H.; Hu, P.; Wang, B.-Q.; Shimizu, Y. (Chem. Commun., 2011)

(untitled) - Vautravers, N. R.; Regent, D. D.; Breit, B. (Chem. Commun., 2011)